The Effect of Learning Environment on Student Motivation and Student Achievement (Literature Review Study) - Bimaruci Hazrati Havidz, Hazimi; Mujakiah, Nur (International Journal of Psychology and Health Science, 2023)
A literature review article (literature review study) on the effects of the work environment on student motivation and performance is an academic article that aims to establish a research hypothesis about the effects of variables for further research within the framework of psychology. The writing method of this literature review article is the library search method from online media such as Google Scholar, Mendeley and other online academic media. The findings of this literature review article are: 1) learning environment affects student motivation; 2) learning environment affects student achievement; 3) student motivation affects student performance. In addition to the above exogenous variables that affect endogenous variables, there are other factors including: parent education, parent and teacher guidance.